Data subject rights in the era of AI - Rute Silva Gomes (Quaderns IEE)
The widespread use of AI and its increasing capabilities, as well as the impact of decisions made by AI systems on the lives of natural persons, have prompted discussions on the extent to which existing regulations are well equipped to deal with these systems.